Microstructural Investigation of Discarded NdFeB Magnets After Low-Temperature Hydrogenation - Habibzadeh, Alireza; Kucuker, Mehmet Ali; Cakir, Oznur; Gokelma, Mertol (SPRINGER, 2024)
Due to continuously increasing demand and limited resources of rare-earth elements (REEs), new solutions are being sought to overcome the supply risk of REEs. To mitigate the supply risk of REEs, much attention has recently been paid to recycling. Despite the more common recycling methods, including hydrometallurgical and pyrometallurgical processes, hydrogen processing of magnetic scrap (HPMS) is still in the development stage. Magnet-to-magnet recycling via hydrogenation of discarded NdFeB magnets provides a fine powder suitable for the production of new magnets from secondary sources. One of the crucial aspects of HPMS is the degree of recovery of the magnetic properties, as the yield efficiency can easily reach over 95%. The amount, morphology, and distribution of the Nd-rich phase are the key parameters to achieve the excellent performance of the magnet by isolating the matrix grain. Therefore, a better insight into the microstructure of the matrix grains and the Nd-rich phase before and after hydrogenation is essential. In this study, a low-temperature hydrogenation process in the range of room temperature to 400 degrees C was conducted as the first step to recycle NdFeB magnets from discarded hard disk drives (HDDs), and the hydrogenated powder was characterized by electron microscopy and X-ray diffraction. The results show that there are three different morphologies of the Nd-rich phase, which undergo two different transformations through oxidation and hydride formation. While at lower temperatures (below 250 degrees C) the degree of pulverization is higher and the experimental evidence of hydride formation is less clear, at higher temperatures the degree of pulverization decreases. The formation of neodymium hydride at higher temperatures prevents further oxidation of the Nd-rich phase due to its high stability.
Keywords: Hydrogen decrepitation; Magnet-to-magnet recycling; Nd-rich phase; HPMS; FE-B MAGNETS; CRYSTAL-STRUCTURE; GRAIN-BOUNDARY; HYDRIDE; COERCIVITY; PRESSURE; KINETICS; ALLOYS; Science & Technology - Other Topics; Metallurgy & Metallurgical Engineering